2020
DOI: 10.1017/s0142716420000442
|View full text |Cite
|
Sign up to set email alerts
|

Does learner cognition count on modality? Working memory and L2 morphosyntactic achievement across oral and written tasks

Abstract: This study investigates how working memory (WM) abilities are implicated in second language (L2) learners’ (a) morphosyntactic achievement and (b) perceptions of required mental effort and task difficulty under oral versus written task modality conditions. Beginning-level learners of L2 Spanish completed two computerized focused tasks in which they produced output and received feedback in oral form (Speaking group) or written form (Writing group). Two grammatical structures varying in their relative level of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…Indeed, empirical evidence suggests that individual differences in WM capacity predict grammar development (Lado, 2017;Serafini & Sanz, 2016; for a comprehensive review, see McCormick & Sanz, 2022), and comprehension (Sagarra, 2017), for example. The contribution that WM capacity makes to production, including writing, has received less attention, but recent studies (see Table 1) show that individual differences in WM influence second language written texts (but see Manchón et al, 2023, in this issue) and writing processes (especially regarding pausing behavior; see Révész et al, 2023 andTorres, 2023 in this issue); that task demands and different modes of production -oral or written-differentially tax second language processes that involve WM; and that, regardless of individual WM skills, writing tasks afford better opportunities for effective grammar learning compared with oral tasks, as evidenced in Zalbidea (2017) and Zalbidea and Sanz (2020).…”
Section: The Role Of Ids In Writing: Working Memory and Writingmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, empirical evidence suggests that individual differences in WM capacity predict grammar development (Lado, 2017;Serafini & Sanz, 2016; for a comprehensive review, see McCormick & Sanz, 2022), and comprehension (Sagarra, 2017), for example. The contribution that WM capacity makes to production, including writing, has received less attention, but recent studies (see Table 1) show that individual differences in WM influence second language written texts (but see Manchón et al, 2023, in this issue) and writing processes (especially regarding pausing behavior; see Révész et al, 2023 andTorres, 2023 in this issue); that task demands and different modes of production -oral or written-differentially tax second language processes that involve WM; and that, regardless of individual WM skills, writing tasks afford better opportunities for effective grammar learning compared with oral tasks, as evidenced in Zalbidea (2017) and Zalbidea and Sanz (2020).…”
Section: The Role Of Ids In Writing: Working Memory and Writingmentioning
confidence: 99%
“…Also worthy of comment is that aptitude has been predicted to be fully implicated in communicative practice, in monitoring output, and in learning from producing comprehensible output, which would surely include comprehensible written output. Equally relevant from a pedagogical angle would be a consideration of the attested effects of IDs (including L2 proficiency and working memory) in learning and task performance across modalities (Zalbidea, 2021; Zalbidea & Sanz, 2020; see a review in Johnson, 2021; Manchón & Vasylets, 2019; Vasylets & Gilabert, 2021).…”
Section: Writing and Sla Ids Research The Relevance Of Working Memorymentioning
confidence: 99%
“…The final contribution to this issue, from Pawlak and Biedroń, is titled "Working memory as a factor mediating explicit and implicit knowledge of English grammar." As noted previously, many researchers conclude that WM is a part of LA (Doughty, 2019 andrecent work by Jackson, 2020;Vasylets & Marín, 2020;Zalbidea & Sanz, 2020). As in the Lambelet piece, Pawlak and Biedroń report on a subset of results from a larger scale study.…”
mentioning
confidence: 90%
“…Concerning morphosyntax in L2 Spanish writing, in particular, Zalbidea’s (2017) study found a significant negative correlation between WM and Spanish gender agreement errors in the writing of participants who completed a complex writing task. However, Zalbidea and Sanz (2020) reported that WM was more strongly associated with accurate morphosyntactic performance in their speaking condition relative to the written one; however, visuospatial WM contributed to written accuracy for a less salient Spanish linguistic structure. In a study examining the relationship between WM measures and L2 writing processes, Révész et al (2017) found the following significant correlations: (a) visuospatial span and less frequent pauses to gaze at task instructions, (b) operation span measuring updating ability and fewer pauses between paragraphs, and (c) color–shape task measuring task-switching abilities and longer pauses between sentences.…”
Section: Introductionmentioning
confidence: 96%